KEMAMPUAN MENGIDENTIFIKASI UNSUR-UNSUR TEKS DRAMA SISWA KELAS VIII SEMESTER II SMP NEGERI 4 LEMBANG JAYA TAHUN AJARAN 2022/2023 - Srianti, Yunita; Wirasty B., Rini; Putri, Mega (JELISA (Jurnal Edukasi dan Literasi Bahasa), 2023)
This research aims to describe the ability to identify the elements of drama texts for class VIII Semester II students at SMP Negeri 4 Lembang Jaya for the 2022/2023 academic year. This type of research is quantitative research using descriptive methods. The population of this research was class VIII students of SMP Negeri 4 Lembang Jaya, Solok Regency. The research sample for class VIII C students registered in that academic year was 72 people, with a sample size of 24 people. The research sampling technique was carried out using a purposive sampling technique by taking subjects from each stratum or each region determined to be balanced or comparable with the number of subjects in each stratum or region. The data collection technique in this research is a performance test. Data analysis techniques include reading, correcting and scoring student test results, converting raw scores into grades, classifying student grades on a scale of 10, making a histogram, and summarizing the results in the form of a thesis. The results of the research on the ability to identify the elements of a drama text, the average score of students' ability to identify plot elements, namely 94.33, is in very good qualifications, students' ability to identify elements of characterization, namely 95.75, is in very good qualifications, students' ability to identify dialogue elements, namely 100, are in perfect qualifications, students' ability to identify elements, namely 100, is in perfect qualifications, students' ability to identify theme elements is 55.04, is in almost sufficient qualifications, students' ability to identify message elements, namely 88.66, is in very good qualifications. . Based on the qualifications above, it can be concluded that the students' ability to identify the elements of drama texts in class VIII Semester II of SMP Negeri 4 Lembang Jaya for the 2022/2023 academic year has been able to identify drama texts in very good qualifications with a mastery level of 86-95% with a score average 89.06.